2022
DOI: 10.1101/2022.06.08.494710
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Luminal progenitors undergo partial epithelial-to-mesenchymal transition at the onset of basal-like breast tumorigenesis

Abstract: Defects in double-strand repair mechanisms - both through germline or somatic inactivation of repair genes - is a hallmark of basal-like breast cancers. In this genetically-unstable context, a recurrent shift in cell identity occurs within the mammary epithelium. Basal-like tumors have indeed been proposed to originate from luminal progenitor (LP) cells yet tumor-initiating events remain poorly understood. Here, we map state transitions at the onset of basal-like tumorigenesis, using a Brca-1 deficient mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 77 publications
2
4
0
Order By: Relevance
“…Furthermore, in agreement with previous studies, we found that, in Brca1/p53-deficient epithelium, a non-negligible fraction of p16 + cells was abnormally cycling, as shown by their Ki67 status (Fig. 5 E; [ 40 , 41 ]. Of interest, we found that the amount of cycling p16 + cells was reduced in Itgα6-deficient glands, predominantly in normal-looking epithelial structures, suggesting cell cycle misregulation in cells expressing p16 in preneoplastic glands (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in agreement with previous studies, we found that, in Brca1/p53-deficient epithelium, a non-negligible fraction of p16 + cells was abnormally cycling, as shown by their Ki67 status (Fig. 5 E; [ 40 , 41 ]. Of interest, we found that the amount of cycling p16 + cells was reduced in Itgα6-deficient glands, predominantly in normal-looking epithelial structures, suggesting cell cycle misregulation in cells expressing p16 in preneoplastic glands (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Among invasive breast cancer, basal-like tumors are characterized by the high expression of the cell cycle inhibitor p16 at the transcriptional level [ 40 ]. Moreover, the presence of a p16-expressing luminal cell population in preneoplastic Blg-Cre;Brca1 F/F ;Trp53 F/F mammary tissue has been recently reported [ 41 ]. In agreement with these recent findings, we detected p16 expression in luminal cells (K8 + /α-SMA) from 5-month-old Brca1 mutant mice, but not in control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These trends are further supported by recent experimental observations that luminal progenitors, the proposed cell of origin of basal-like tumors, undergo a pEMT at onset of tumorigenesis (Landragin et al, 2022). Moreover, mammary basal epithelial cells have been shown to exhibit a pEMT state, i.e.…”
Section: Resultssupporting
confidence: 75%
“…For instance, mature mammary luminal epithelial cells can give rise to Krt14 and Sox9-expressing basal-like carcinomas that can metastasize (Kern et al, 2022). Similarly, basal-like tumorigenesis involves luminal-to-basal reprogramming with gain in stemness (Christin et al, 2020; Landragin et al, 2022). Further, luminal-basal hybrid cells can express NP63 (basal marker) while maintaining functional levels of ER-alpha (associated with luminal phenotype) (Padua et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our study further highlights a mechanistic link between OIS and EMP during malignant transformation. Strengthening our observations, recent studies have used a pan-cancer scRNA-seq approach to show recurrent signatures associated with EMP and senescence at tumor initiation and over the course of malignant transformation (47)(48)(49). Cellular senescence is a stress response that is generally considered to irreversibly arrest the cell cycle following a variety of intrinsic and extrinsic stressors such as shortening of chromosomal termini, DNA damage, oxidative stress, oncogenic insults, or inactivation of tumor suppressors (50).…”
Section: Discussionmentioning
confidence: 56%